2020
DOI: 10.1016/j.ekir.2020.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Plasma Oxalate Concentration in Patients With CKD

Abstract: Introduction: Alterations in oxalate homeostasis are associated with kidney stone disease and progression of chronic kidney disease (CKD). However, accurate measurement of plasma oxalate (P Ox) concentrations in large patient cohorts is challenging as prompt acidification of samples has been deemed necessary. In the present study, we investigated the effects of variations in sample handling on P Ox results and examined an alternative strategy to the established preanalytical procedures. Methods: The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Studies have shown a good correlation between spot level and 24h excretion, with no significant diurnal pattern of oxalate excretion (18)(19). In individuals with stage 4 and 5 CKD, urinary oxalate excretion decreases and plasma oxalate starts to rise (20). Plasma oxalate levels are used to monitor primary hyperoxaluria patients with CKD and on dialysis, prior to transplantation (21)(22).…”
Section: Oxalate Metabolism and Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown a good correlation between spot level and 24h excretion, with no significant diurnal pattern of oxalate excretion (18)(19). In individuals with stage 4 and 5 CKD, urinary oxalate excretion decreases and plasma oxalate starts to rise (20). Plasma oxalate levels are used to monitor primary hyperoxaluria patients with CKD and on dialysis, prior to transplantation (21)(22).…”
Section: Oxalate Metabolism and Measurementmentioning
confidence: 99%
“…Accurate measurement of plasma oxalate concentration is however challenging. Prompt acidification or freezing of samples and storage at -80°C until acidification is required to prevent conversion of plasma ascorbate to oxalate (20). Moreover, plasma oxalate levels do not correlate well with eGFR and show significant intraindividual variation in patients with primary hyperoxaluria (21).…”
Section: Oxalate Metabolism and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent article by Pfau et al. , 1 “Assessment of Plasma Oxalate Concentration in Patients With CKD,” they reported a new simple procedure for evaluating plasma oxalate (POx) concentration that enabled the investigation of a large cohort of patients with chronic kidney disease (CKD). 1 They measured POx in 1826 patients with CKD and found stable results; furthermore, they reaffirmed a negative correlation between the estimated glomerular filtration rate and POx.…”
mentioning
confidence: 99%
“…The Author Replies: We thank Oka et al. for the precise summary of our study “Assessment of plasma oxalate concentration in patients with CKD” 1 and their excellent suggestions for future investigations. As proposed, we added a regression line to the scatter plot that illustrates the correlation between estimated glomerular filtration rate and plasma oxalate concentration ( Figure 1 ) with the correlation coefficient r being −0.22 (Spearman correlation; P < 0.001).…”
mentioning
confidence: 99%